Shura in mixed-faith family relations: an approach to strengthen family bonds in Sabah - Mohd Nazmi Mohd Khalli,; Suraya Sintang,; Zaenuddin Hudi Prasojo, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Shura is an ideal Islamic approach in negotiations, meetings and decision-making characterized by an inclusive consensus mechanism. Shura allows all parties to speak and is not biased perspectives, prejudiced or monopolizing individuals. Therefore, this shura approach is potentially being practiced in mixed-faith family relations between new Muslims and non-Muslim families. This is because the relations between new Muslims and non-Muslim families show apparent contradictions due to religious mixing and conversion to Islam. Therefore, this study aims to discuss the experiences of mixed-faith families through the experiences of new Muslims and non-Muslim families to strengthen family bonds. A total of 10 informants were interviewed in depth in various places around Sabah. The findings explain that the experiences of mixed-faith families in managing religious differences align with the highlighted concept of shura. These approaches include joint decision-making, hikmah-based (wisdom) dialogue, and continuous gatherings in various activities. Through this shura approach, family bonds do not only strive to avoid disputes due to religious differences. But also aim to strengthen the family bond that is to be maintained. Therefore, the shura approach through the experiences of mixed-faith families need to be upheld as an initiative to manage differences within a multi-religious and multi-cultural society.